PATIENT SAFETY AND INFECTION CONTROL IN THE INTENSIVE CARE UNIT: BIBLIOGRAPHIC ANALYSIS FOR PREVENTION AND HEALTH PROMOTION MEASURES - Kelly Araújo Silva Melo, Geni; Paula Santos e Silva, Ana (Health and Society, 2023)
This study is bibliographic, with a qualitative, descriptive and exploratory approach. The bibliographic study takes place from a data survey, which uses some instruments, such as: books, scientific articles, theses, dissertations, legislation and other published sources, in which data collection took place with 10 articles, in October 2023 The studies demonstrated the importance of continuing education, standardization of actions, implementation of protocols and guidelines that help manage patient safety in the ICU, as there is still a lack of knowledge on the part of health professionals and also of scientific knowledge. Numerous outcomes were cited in the research found, however, the importance of basic care was perceived, such as hand washing, precarious equipment, lack of training, and lack of preparation of the healthcare team.